A new species of the genus Rhabdophis Fitzinger, 1843 (Squamata: Colubridae) from the Hoang Lien range, northwest Vietnam - Kane, Daniel; Tapley, Benjamin; La, Toi Van; Nguyen, Luan Thanh (Zootaxa, 2023)
We describe a new species of the Natricinae genus Rhabdophis Fitzinger, 1843 from the Hoang Lien range, northwest Vietnam. The new species is distinct from all congeneric species on the grounds of morphometric and molecular data. The new species is most similar to Rhabdophis leonardi in terms of morphology but can be distinguished from it based on differences in maxillary tooth count, scalation, and genetic data. A sequence on GenBank from a Rhabdophis specimen collected in Honghe, Yunnan, China was identical to the species we describe, and it is likely that the new species is not restricted to Vietnam. As a priority, future work should focus on determining the distribution of this species, as well as understanding population and life history traits such as reproductive rate.